Lipidomic Profiling of Mastoid Bone and Tissue from Patients with Chronic Otomastoiditis - Farbod Fazlollahi; Kessiri Kongmanas; Nongnuj Tanphaichitr; Jeffrey Suh; Kym Faull; Quinton Gopen (International Archives of Otorhinolaryngology, 2015)
Abstract